NATIVE VS NON-NATIVE ENGLISH TEACHERS - Masrizal Masrizal (Jurnal Ilmiah Didaktika, 2013)
Although the majority of English language teachers worldwide are non-native English speakers (NNS), no research was conducted on these teachers until recently. A pioneer research by Peter Medgyes in 1994 took quite a long time until the other researchers found their interests in this issue. There is a widespread stereotype that a native speaker (NS) is by nature the best person to teach his/her foreign language. In regard to this assumption, we then see a very limited room and opportunities for a non native teacher to teach language that is not his/hers. The aim of this article is to analyze the differences among these teachers in order to prove that non-native teachers have equal advantages that should be taken into account. The writer expects that the result of this short article could be a valuable input to the area of teaching English as a foreign language in Indonesia.